Augmented Reality as a Medium for Improved Telementoring. (21st March 2019) - Rojas-Muñoz, Edgar; Andersen, Dan; Cabrera, Maria Eugenia; Popescu, Voicu; Marley, Sherri; Zarzaur, Ben; Mullis, Brian; Wachs, Juan P
Abstract: Combat trauma injuries require urgent and specialized care. When patient evacuation is infeasible, critical life-saving care must be given at the point of injury in real-time and under austere conditions associated to forward operating bases. Surgical telementoring allows local generalists to receive remote instruction from specialists thousands of miles away. However, current telementoring systems have limited annotation capabilities and lack of direct visualization of the future result of the surgical actions by the specialist. The System for Telementoring with Augmented Reality (STAR) is a surgical telementoring platform that improves the transfer of medical expertise by integrating a full-size interaction table for mentors to create graphical annotations, with augmented reality (AR) devices to display surgical annotations directly onto the generalist's field of view. Along with the explanation of the system's features, this paper provides results of user studies that validate STAR as a comprehensive AR surgical telementoring platform. In addition, potential future applications of STAR are discussed, which are desired features that state-of-the-art AR medical telementoring platforms should have when combat trauma scenarios are in the spotlight of such technologies.